EFFECT OF INSECT POLLINATORS ON FRUIT SETTING ON MANGO (Mangifera indica L.) - Aslam, Muhammad; Razaq, Muhammad; Hussain, Saqib; Akhter, Waheed (Journal of Research (Science), 2004)
Effect of insect pollinators on fruit setting on mango (Mangifera indica L.), variety “Dusehri” was studied in a mango orchard at Mauza Lutfabad near Multan from 10 March to 01 April 2003. Twenty plants were selected for study from an acre of mango orchard. The age of the plants was seven years. Before the start of blooming, one inflorescence from each of the ten plants was encaged to prevent the entry of pollinators and one inflorescence on each plant was kept uncaged. At the end of March, after the fruit setting was over, total numbers of fruiting bodies were recorded from each of the caged and uncaged inflorescence. Mean number of fruits set was significantly higher on uncaged (visited by pollinators) inflorescence than those on caged (not visited by pollinators). Numbers of fruits set per inflorescence on uncaged and caged mango trees were 42.5 and 28.3 per inflorescence, respectively.